Ibrexafungerp, a Novel Oral Triterpenoid Antifungal in Development: Overview of Antifungal Activity Against Candida glabrata - Gamal, Ahmed; Chu, Sherman; McCormick, Thomas S.; Borroto-Esoda, Katyna; Angulo, David; Ghannoum, Mahmoud A. (Frontiers in Cellular and Infection Microbiology, 2021)
Systemic infections caused by Candida species are an important cause of morbidity and mortality among immunocompromised and non-immunocompromised patients. In particular, Candida glabrata is an emerging species within the Candida family that causes infections ranging from superficial to life-threatening systemic disease. Echinocandins and azoles are typically the first-line therapies used to treat infections caused by C. glabrata, however, there is an increasing prevalence of resistance to these antifungal agents in patients. Thus, a need exists for novel therapies that demonstrate high efficacy against C. glabrata. Ibrexafungerp is a first-in-class glucan synthase inhibitor with oral availability developed to address this increasing antifungal resistance. Ibrexafungerp demonstrates broad in vitro activity against wild-type, azole-resistant, and echinocandin-resistant C. glabrata species. Furthermore, ibrexafungerp has shown efficacy in low pH environments, which suggests its potential effectiveness in treating vulvovaginal candidiasis. Additional preclinical and clinical studies are needed to further examine the mechanism(s) of ibrexafungerp, including acting as a promising new agent for treating C. glabrata infections.